Research on the Theory of Optical Transmission for Bragg Fiber With High-Index-Core - Liu, Daojun; Zhang, Ji (Frontiers in Physics, 2020)
The paper analyzes the two theories of conducted light signal for Bragg fiber with high-index core, namely total internal reflection and photonic bandgap. From the perspective of the wave equation, the distribution of the electromagnetic field and the conditions for forming the guided mode when the optical signal is transmitted in the core of fiber are explained. The analysis of photonic bandgap adopts the band structure principle of natural crystals for analogy. Then, the formation process of the photonic bandgap is elaborated on.